The impact of tahfiz programme on students’ religiosity: a case study - Mohd Ishak, Noor Farhanah; Nik Abdullah, Nik Md. Saiful Azizi; Muhammad Isa, Rabi'atul Athirah (Penerbit UnIPSAS, 2023)
This study aimed to investigate the impact of the tahfiz programme on students' religiosity at Sekolah Menengah Agama Dato Haji Tan Ahmad in Negeri Sembilan. It was conducted using a qualitative approach, selecting six students through non-probability purposive sampling, comprising three males and three females. Data was collected through face-to-face semi-structured interviews, employing a single case study design. The analysis involved coding, categorising, and identifying sub-themes to develop the main theme. The findings revealed that the tahfiz programme had a positive effect on students' religiosity, influenced by both internal and external factors. Internally, the religious environment within the tahfiz programme and the guidance provided by the tahfiz teachers played significant roles. Externally, the positive perception of outsiders towards tahfiz students' religious practices also contributed to the enhancement of students' religiosity. The tahfiz programme had various effects on students, impacting their faith, worship, akhlaq (moral values), and overall character. The results suggest that attending a tahfiz program can significantly contribute to the spiritual development of students. Therefore, it is recommended for schools to incorporate Quranic learning to facilitate the growth of students' religious aspects.